CD226 Deficiency Alleviates Murine Allergic Rhinitis by Suppressing Group 2 Innate Lymphoid Cell Responses. (7th July 2022) - Xie, Yang; Zhang, Yuan; Zhu, Tianxiao; Ma, Jingchang; Duan, Chujun; Yang, Lu; Wang, Tingting; Zhuang, Ran; Bian, Ka; Lu, Lianjun
Abstract : Allergic rhinitis (AR) is an immunoglobulin E-mediated type 2 inflammation of the nasal mucosa that is mainly driven by type 2 helper T cells (Th2) and type 2 innate lymphoid cells (ILC2s). CD226 is a costimulatory molecule associated with inflammatory response and is mainly expressed on T cells, natural killer cells, and monocytes. This study is aimed at elucidating the role of CD226 in allergic inflammatory responses in murine AR using global and CD4 + T cell-specific Cd226 knockout (KO) mice. AR nasal symptoms were assessed based on the frequency of nose rubbing and sneezing. Hematoxylin and eosin and periodic acid–Schiff staining and quantitative real-time PCR methods were used to determine eosinophils, goblet cells, and ILC2-associated mRNA levels in the nasal tissues of mice. CD226 levels on ILC2s were detected using flow cytometry, and an immunofluorescence double staining assay was employed to determine the number of ILC2s in the nasal mucosa. The results showed that global Cd226 KO mice, but not CD4 + T cell-specific Cd226 KO mice, exhibited attenuated AR nasal symptoms. Eosinophil recruitment, goblet cell proliferation, and Th2-inflammatory cytokines were significantly reduced, which resulted in the alleviation of allergic and inflammatory responses. ILC2s in the murine nasal mucosa expressed higher levels of CD226 after ovalbumin stimulation, and CD226 deficiency led to a reduction in the proportion of nasal ILC2s and ILC2-related inflammatory gene expression. Hence, the effect of CD226 on the AR mouse model may involve the regulation of ILC2 function rather than CD4 + T cells.